Development of PISA-Type Questions and Activities in a Smartphone Context - Mutia Febri Mouli; Zulkardi Zulkardi; Ratu Ilma Indra Putri (Jurnal Pendidikan Matematika, 2023)
Sometimes our smartphone's internal storage is complete, and we must download an application that is very necessary at that time; this is where numeracy plays a role in solving this problem, namely the way we download the desired application with a complete smartphone's internal storage. This study aims to produce valid and practical PISA-type questions and activities using a smartphone context and potentially effective on students' numeracy skills. This design research-type development study comprised a preliminary and formative evaluation phase consisting of the design stage, self-evaluation stage, expert review stage, one-to-one stage, and small group stage. This research used question grids, question cards, assessment rubrics, lesson plans, PISA-type questions, and student activity sheets as its tools. This study was initiated owing to the insufficient numeracy skills of Indonesian students. This study focuses on seventh-grade students at secondary school number 59 Palembang, Indonesia. The qualitative findings of this research are based on field data collected through walkthroughs, observations, tests, interviews, and document reviews. This research yielded PISA-type questions and activities, namely four activity questions and six evaluation questions with smartphone context that seventh graders may utilize to develop their numeracy abilities. In conclusion, PISA-type questions and activities in the context of smartphones can be used in classroom learning to strengthen students' numeracy skills.